Perception of Respondents on Factors Affecting Management of Nursing Education Institutes - Dangol, Bhuwan Kumari; Thapa, Narbada (Journal of Advanced Academic Research, 2021)
Management in education institute entails working with and through teachers, non teaching staff and students to get things done effectively. A descriptive cross-sectional study design was used to find out the management of nursing education institutes in selected colleges at Kathmandu valley. Data was collected in 2019 from 14 colleges. Sample size was 620, including 14 administrators, 229 faculties and 377 bachelor level final year nursing students. Ethical approval was taken from Nepal health research council. Self-administered structured questionnaire was used to collecting data and analysis was done in SPSS version 16.Keys factors were identified that may affect the management of nursing education institutes (NEI). All most all administrators agreed in all indicators. But there was different opinion on faculties and students. Highest percent of faculties disagreed on visions, mission, staffs understood (70%), class schedule, clinical supervision and students’ teacher ratio, nursing leadership (17%) and resource availability. Fifteen percent students disagreed in functioning alumni, library facility, strategic plan and function of executive committee (36.1%), use of operation plan, lesson plan (22.3%), class schedule (16.4%), and facility of skill laboratory (9.1%), clinical supervision (27.6%) and proper students’ teacher ratio (36.3%). In quality assurance system majority of the facilities disagreed and all most all students undecided. Analysis of variations between group (administrators, faculties, students) found statistical significance (p-value <0.05). So it is concluded the perception of students, faculties and administrator were found different on management of the nursing education institutes.